Analyzing Traditional Moke Gastronomy Within Creative Economy Transformation and National Economic Strengthening - Bhenediktha Yulia Cindy Putri Iku; Lidya Selviana Orowala; Yohana Bhanda; Mandalia Lofita Rihi; Antonio G. Pratama; Claudius Luis; Gregorius Wilbar Nong Sobar (Yayasan Cerdas Pedia Indonesia, 2026)
This research examines the strategic position of Moke, a traditional beverage from East Nusa Tenggara, within the framework of gastronomy and creative economy. Employing a qualitative descriptive approach with the Miles and Huberman model, the study analyzes Moke’s sociocultural significance and economic efficiency. Results indicate that Moke functions as a vital instrument of social cohesion and ethnic identity in Sikka Regency. From a microeconomic perspective, the industry demonstrates high feasibility with an R/C ratio of 3.5, following Alfred Weber’s resource-oriented location theory. Furthermore, innovations like Moke Triple highlight the potential for modernization through standardization and creative branding. Nationally, the food and beverage sector remains a resilient GDP contributor, growing by 5.9% in 2024. This study concludes that integrating cultural preservation with digital transformation and robust regional regulations is essential for elevating Moke into a globally competitive creative commodity. Strategic government support is crucial for optimizing this local asset for strengthening.